2016
DOI: 10.1038/srep30907
|View full text |Cite
|
Sign up to set email alerts
|

Increasing strength and conductivity of Cu alloy through abnormal plastic deformation of an intermetallic compound

Abstract: The precipitation strengthening of Cu alloys inevitably accompanies lowering of their electric conductivity and ductility. We produced bulk Cu alloys arrayed with nanofibers of stiff intermetallic compound through a precipitation mechanism using conventional casting and heat treatment processes. We then successfully elongated these arrays of nanofibers in the bulk Cu alloys to 400% of original length without breakage at room temperature using conventional rolling process. By inducing such an one-directional ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…The ductility of the Al–33Zn alloy with Cu addition might be increased by the fast discontinuous precipitation that removed heterogeneous, large, precipitated particles affecting GB stability. Generally, the discontinuous precipitate was formed easily when a certain condition was satisfied; e.g., when there was a high driving force for precipitation, a large high-angle GB as a discontinuous precipitation site and an anisotropic crystal structure, which led to a different interfacial energy of the interface between precipitate and matrix 21 26 . The results of this study show that Cu addition reduces the interface energy between the Zn phase and Al matrix, which causes a drastic decrease in precipitate size and encourages discontinuous precipitation at GBs during solidification or solution treatment (see Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
“…The ductility of the Al–33Zn alloy with Cu addition might be increased by the fast discontinuous precipitation that removed heterogeneous, large, precipitated particles affecting GB stability. Generally, the discontinuous precipitate was formed easily when a certain condition was satisfied; e.g., when there was a high driving force for precipitation, a large high-angle GB as a discontinuous precipitation site and an anisotropic crystal structure, which led to a different interfacial energy of the interface between precipitate and matrix 21 26 . The results of this study show that Cu addition reduces the interface energy between the Zn phase and Al matrix, which causes a drastic decrease in precipitate size and encourages discontinuous precipitation at GBs during solidification or solution treatment (see Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
“…The highest tensile strength of DPR specimen was mainly caused by the decrease in the radii of aligned Ni 2 Si nanofibers and the interdistance between them. It has been shown that an increase in tensile strength induced by work hardening is less than 60% of that brought by the nanofiber array formation in Cu-6Ni-1.4Si-0.1Ti alloys subjected to cold-rolling with 90% reduction in area [8]. The electrical conductivity of the CP and DP specimen was 25 and 44%IACS, respectively (Fig.…”
Section: Tensile Properties Of Precipitate Strengthened Cu-6ni-15si Alloymentioning
confidence: 97%
“…Simultaneous increase in electrical conductivity and tensile strength of precipitate strengthened Cu-Ni-Si alloys is often extremely difficult, because a decrease in electric conductivity is inevitably caused by the available strengthening mechanism. Using Cu-6Ni-1.4Si-0.1Ti alloys, Han et al [8] fabricated alloys with fully DP phases through a prolonged aging (overaging) process. The product was then mechanically rolled with 90% reduction in area.…”
Section: Microstructure Of the Cold-rolled Dp Specimenmentioning
confidence: 99%
See 1 more Smart Citation
“…Çok ince taneli (UFG) malzeme üretimi, genel itibarıyla aşağıdan-yukarıya (bottom-up) ve yukarıdan-aşağıya (top-down) yaklaşımları olmak üzere iki farklı yol ile gerçekleştirilebilmektedir (Zhu et al 2004). Bottom-up yönteminde, genellikle nano-tozlar yoğunlaştırılarak, konsolide edilirken (Gleiter 2000); top-down yaklaşımın temelinde ise kütlesel halde kaba taneli malzemeye uygulanan aşırı plastik deformasyon (severe plastic deformation, SPD) neticesinde çok ince taneli yapıya ulaşma yatmaktadır (Khereddine et al 2013, Han et al 2016. Geliştirilmiş pek çok SPD tekniği olmakla beraber; eş kanallı açısal pres/EKAP (equalchannel angular pressing, ECAP) ve yüksek basınç altında burma (high pressure torsion, HPT) en yaygın olarak uygulanan yöntemlerdir (Smirnova et al 1986, Segal 1977, Segal et al 1981, Gleiter 1989, Senkov et al 2004, Valiev and Langdon 2006.…”
Section: Introductionunclassified